Are Transcutaneous Oxygen and Carbon Dioxide Determinations of Value in Pulmonary Arterial Hypertension?. (May 2015) - Tonelli, Adriano R.; Alkukhun, Laith; Cikach, Frank; Ahmed, Mostafa; Dweik, Raed A.
Abstract: Background: We hypothesized that transcutaneous gas determinations of O2 and CO2 (TcPO2 and TcPCO2 ) are associated with the severity of PAH. Methods: In this cross‐sectional study, we included consecutive patients with PAH (group 1 PH; n = 34). Transcutaneous gas determinations were compared to those of age‐ and gender‐matched healthy controls ( n = 14), nongroup 1 PH ( n = 19) or patients with high estimated RVSP on echocardiography but without hemodynamic evidence of PH ( n = 12). Results: In patients with PAH, TcPO2, and TcPCO2 were significantly associated with PaO2 ( R = 0.44, p = 0.03) and PaCO2 ( R = 0.77, p < 0.001), respectively. TcPO2 /FiO2 (mean difference: −65.0 [95% CI: −121.3, −8.7]) and TcPCO2 (mean difference: −7.4 [95% CI: −11.6, −3.1]) were significantly lower in patients with PAH than healthy controls. TcPCO2 was useful in discriminating PAH patients from other individuals (AUC: 0.74 [95% CI: 0.62, 0.83]). TcPO2 /FiO2 ratio was significantly associated with mean PAP, TPG, PVR, CI, SVI, DLCO, six‐minute walk distance and components of the CAMPHOR questionnaire. Conclusions: Transcutaneous pressure of CO2 was lower in patients with PAH. Transcutaneous pressure of O2 over inspired fraction of O2 ratio was inversely associated with severity of disease in patients with PAH.